Optimized Passive Coupling Control for Biped Robot - Lipeng YUAN; Amur Al Yahmedi; Liming Yuan (Institute of Advanced Engineering and Science, 2013)
A popular hypothesis regarding legged locomotion is that humans and other large animals walk and run in a manner that minimizes the metabolic energy expenditure for locomotion. Here, we just consider the walking gait patterns. And we presented a hybrid model for a passive 2D walker with knees and point feet. The dynamics of this model were fully derived analytically. We have also proposed optimized virtual passive and virtual coupling control laws. This is also a simple and effective gait-generation method based on this kneed walker model, which imitates the energy behavior in every walking cycle. The control strategy is formed by taking into account the features of mechanical energy dissipation and restoration. Following the proposed method, we use computer optimization to find which gaits are indeed energetically optimal for this model. And we also prove some walking rules maybe true by the results of simulations. DOI: http://dx.doi.org/10.11591/telkomnika.v11i6.2612